Pemanfaatan Literatur dalam Menunjang Prestasi Belajar Siswa Kelas XI IPS SMA Negeri 6 Padang - Ilham, Fadhli Aulia; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this paper is to describe: (1) the activities carried out by the students of class XI IPS SMA 6 Padang in the school library, (2) the use of literature by the students of class XI IPS SMA 6 Padang in the school library, and (3) the constraints faced by students of class XI IPS SMA 6 Padang in utilizing literature. Data were collected through observation and interviews with the students of class XI IPS SMA 6 Padang. Analyzing data descriptively. By analyzing the data, it was concluded the following. First, the activities carried class XI IPS SMA 6 Padang in the library are learning as well as searching and sorting of information to support learning activities that can add insight and knowledge of students. Second, the use of literature by the students of class XI IPS SMA 6 Padang with how to read and understand literature as a source of information that students need to have. Third, the constraints faced by students who utilize the literature are: (1) the existing literature in the library is not complete and many are obsolete, (2) the available literature in the library of SMA Negeri 6 Padang is limited so do not have time to look for it, and (3) students do not use the library as a primary source of learning because they think it easier to use electronic media such as the Internet. Keywords: the use of literature; school library